2017
DOI: 10.18869/acadpub.hnmj.27.2.65
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between the Study Habits and the Academic Performance of Medical Sciences Students

Abstract: Introduction: Students' study methods affect their learning and academic achievement, and the resultant process plays a role in the development cognitive and practical skills, and ultimately their future career. Determining the students' study habits and the relationship between their study habits and their academic performance can, therefore, improve their academic achievement, strengthen and modify their study habits. Objective: This study aimed to determine the relationship between the study habits and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 2 publications
0
15
0
1
Order By: Relevance
“…Evidence suggests that learners who do not have enough information about study strategies do not attain effective and stable learning, and therefore will not have an appropriate level of academic achievement 3. In other words, students with better academic achievement use these skills more than those with lower academic achievement 10…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Evidence suggests that learners who do not have enough information about study strategies do not attain effective and stable learning, and therefore will not have an appropriate level of academic achievement 3. In other words, students with better academic achievement use these skills more than those with lower academic achievement 10…”
Section: Introductionmentioning
confidence: 99%
“…In different studies, study skills and habits and their relationship with students’ academic achievement have been studied and different results have been reported 1,3,12. Also, various studies have reported the study habits of students from weak to desirable levels 5,7,10. In this regard, a study conducted on study habits of students in 21 medical universities in Iran showed that 32% of the students suffered from a severe lack of study skills and habits 10.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ebele and Olofu (2017) found out that there is a significant relationship between study habits and students' academic performance. Looyeh, Fazelpour, Masoule, Chehrzad and Leili (2017) investigated the relationship between the Study habits and the Academic performance of Medical Sciences Students found out the significant relationship between the study habits of students and their academic performance. Similarly, Siahi and Maiyo (2015) studied study habits and academic achievement of students also found out that a positive relationship of 0.66 between study habits and academic achievement.…”
Section: Introductionmentioning
confidence: 99%
“…Other predictors of academic performance include components such as age, course, and a history of failures as well as residence. GPA, sex, and emotional intelligence are the best predictors of students' academic performance [22].The parents' level of income on the students' academic achievement. Parents also have a vital role to play in improving their children's academic achievement by offering the social, financial and material support they need to encourage their children to succeed at school [23].…”
Section: Related Review Of Literaturementioning
confidence: 98%